Organic Nutrient Source Allocation and Use in Smallholder Farming Communities: What Are We Missing? - Nyamasoka-Magonziwa, Blessing; Vanek, Steven J.; Carolan, Michael; Ojiem, John O.; Fonte, Steven J. (Frontiers in Sustainable Food Systems, 2021)
Organic nutrient sources (ONS) are managed as a key resource by smallholder farmers to maintain the productivity of soils. Recycling of ONS by applying them to soils is a globally dominant strategy of ecological nutrient management. Understanding how ONS produced on-farm are allocated and what drives farmer decision making around their use is critical for sustainable nutrient management in smallholder agroecosystems. Using focus group discussions and a survey of 184 farming households, we studied socio-economic, socio-cultural, and environmental drivers of ONS allocation and use at farm scales in three contrasting agroecological zones of western Kenya. Farm typologies of ONS management were also developed using cluster analysis based on resource endowment and the connectedness of farmers, management norms, and extension. Our findings suggest that the more resource endowed a farmer is, the more ONS are allocated to the main plot. We also observed that farmers preferred allocating more resources to plots that were considered more fertile. Land tenure had an important influence, in which main plots not owned by farmers were more likely to retain residues. Management of residues depended on gender, seen especially in the burning of legume residues for alternate uses by women farmers and notable since these higher quality residues are often considered key to sustainable soil nutrient management. Farm type was associated with resource endowment and connectedness of farms to extension and other farmers and influenced the allocation of ONS. Finally, there was a strong overarching influence of agroecological zone that often escapes characterization on the allocation of ONS. As research and development organizations continue to engage with smallholder farmers to reduce the burden of global food insecurity, the insights gained by this research will allow better anticipation of drivers and obstacles to improved nutrient management in these farming landscapes and communities.